EVALUATING THE INFLUENCE OF TRYPANOSOMIASIS ON MURINE MODEL USING Corchorus olitorius LEAF EXTRACT AS A TRYPANOCIDAL AGENT - Madaki, Fatima M.; Kabiru, Adamu Y.; Clinton, Ogunrombi D.; Waheed, Sakariyau A.; Ibrahim, Yunusa O. (Bulletin of Natural Sciences Research, 2024)
Trypanosomiasis, a parasitic disease caused by trypanosomes, which are flagellate protozoa transmitted through the bite of the tsetse fly, manifests with symptoms including substantial weight loss, anemia, fever, edema, adenitis, dermatitis, and nervous disorders. This research investigated the impact of trypanosomiasis on a murine model while utilizing Corchorus olitorius leaf extract as a potential trypanocidal agent. An acute toxicity analysis was conducted following Lorke’s method, and the antitrypanosomal efficacy was assessed in rats at doses of 100, 200, and 400 mg/kg over three weeks, monitoring changes in parasitemia count, body weight, and hematological parameters. Additionally, lipid profile, electrolyte concentration, and liver and kidney function were evaluated using standard techniques. The extract demonstrated potent antitrypanosomal activity at 400 mg/kg, significantly reducing the parasitemia count to 11.33±4.16 count/mL compared to the positive control at 2.5 mg/kg body weight doses. Furthermore, the 400 mg/kg dose notably increased packed cell volume and body weight in infected rats. Moreover, there were no significant discrepancies in numerous hematological parameters between the infected treated with diminazene aceturate and the extract’s 400 mg/kg body weight. This study suggests that Corchorus olitorius extract exhibits significant antitrypanosomal, antilipidemic, and erythropoietic effects, mitigating parasitemia count, lipid levels, and oxidative damage by impeding the biochemical activities of trypanosomes through its active constituents. Thus, Corchorus olitorius extract may offer an alternative therapeutic approach for managing trypanosomal infections.